Review of Mechanics and Applications of Auxetic Structures - Mariam Mir; Murtaza Najabat Ali; Javaria Sami; Umar Ansari (Advances in Materials Science and Engineering)
One of the important mechanical properties of materials is Poisson’s ratio, which is positive for most of the materials. However, certain materials exhibit “auxetic” properties; that is, they have a negative Poisson’s ratio. Thus auxetic and non-auxetic materials exhibit different deformation mechanisms. A specific microscopic structure in the auxetic materials is important for maintaining a negative Poisson’s ratio. Based on their distinct nature auxetic materials execute certain unique properties in contrast to other materials, which are reviewed in this paper. Thus auxetic materials have important applications in the biomedical field which are also a part of this review article. Many auxetic materials have been discovered, fabricated, and synthesized which differ on the basis of structure, scale and deformation mechanism. The different types of auxetic materials such as auxetic cellular solids, microscopic auxetic polymers, molecular auxetic materials, and auxetic composites have been reviewed comprehensively in this paper. Modeling of auxetic structures is of considerable importance and needs appropriate stress strain configurations; thus different aspects of auxetic modeling have also been reviewed. Packing parameters and relative densities are of prime importance in this regard. This review would thus help the researchers in determining and deciding the various aspects of auxetic nature for their products.